Effect of a financial incentive (shopping point) on increasing the number of daily walking steps among community-dwelling adults in Japan: a randomised controlled trial - Yasutake Tomata; Fumiya Tanji; Shu Zhang; Saho Abe; Sanae Matsuyama; Yumika Kotaki; Dieta Nurrika; Koichi Matsumoto; Yingxu Liu; Yukai Lu; Shino Bando; Teiichiro Yamazaki; et al. (BMJ Open)
Objective The aim of this study was to investigate the effect of a financial incentive on the number of daily walking steps among community-dwelling adults in Japan.Study design Two-arm, parallel-group randomised controlled trial.Setting/participants We recruited physically inactive community-dwelling adults from Sendai city, Japan. Eligible participants were randomly allocated to an intervention or a wait list control group. Pedometers were used to assess the mean number of daily steps in three periods: baseline (weeks 1–3), intervention (weeks 4–6) and follow-up (weeks 7–9).Intervention The intervention group was offered a financial incentive (shopping points) to meet the target number of increased daily steps in the intervention period.Main outcome measures The primary outcome was an increase in the mean number of daily steps in the intervention and follow-up periods compared with baseline.Results Seventy-two participants (69.4% women; mean age, 61.2±16.2 years; mean number of daily steps at baseline, 6364±2804) were randomised to the intervention (n=36) and control groups (n=36). During the intervention period, the increase in mean daily steps was significantly higher in the intervention group (1650, 95% CI=1182 to 2119) than in the control group (514, 95% CI=136 to 891; p<0.001). However, the difference between groups was not significant at follow-up after the incentives were removed (p=0.311). In addition, compared with controls, a significantly higher proportion of participants in the intervention group showed an increase in mean daily steps of ≥1000 (69.4% vs 30.6%, respectively; OR=5.17, 95% CI=1.89 to 14.08). There were no adverse effects from the intervention.Conclusions The present results suggest that financial incentives are effective in promoting short-term increases in physical activity.Trial registration number UMIN000033276.